Analysis of Pregnant Women's Participation in Covid-19 Vaccination at Cilamaya Health Centre - Shinta Novelia; Siti Syamsiah; Siti Herawati (KHD Production, 2023)
Pregnant women are included in a group that is vulnerable to COVID-19. The maternal mortality rate in Karawang Regency had touched the highest data in West Java in 2021 as many as 117 cases, with 48 cases (41%) of deaths caused by Covid-19. The low number of vaccinations for pregnant women at the Cilamaya Health Center at dose 1 was 54 people (41.17%), dose 2 was 30 people (22%), and dose 3 was 20 people (14.7%). This study aims to determine the relationship between knowledge and the participation of pregnant women in the covid-19 vaccination program, the relationship between family support and the participation of pregnant women in the covid-19 program, and the relationship between anxiety and the participation of pregnant women in the covid-19 program at the Cilamaya Health Center. This research is an analytic observational study with a cross-sectional approach. The sample of this research is 117 pregnant women, taking the total sampling. The instrument for data collection is the Observation Sheet. Data analysis used the Chi-square statistical test with an α value of 5% (α = 0.05). Based on statistical tests, there is a relationship between knowledge of pregnant women p-value 0.003<0.05, a relationship between family support p-value 0.00 <0.001, and no relationship to anxiety p-value 0.406 > 0.05. A significant relationship exists between the mother's knowledge and family support in participating in the Covid-19 vaccination program at the Cilamaya Health Center. It is hoped that pregnant women who have not participated in the Covid-19 vaccination can participate in the Covid-19 vaccine.